1996
DOI: 10.1095/biolreprod55.6.1444
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Intrabursal Administration of Transforming Growth Factor β1 Inhibits Follicle Rupture in Gonadotropin-Primed Mice1

Abstract: We hypothesized that over-expression and/or activation of latent transforming growth factor betas (TGF betas) by various ovarian cell types may lead to disturbances in ovulation and fertilization. To test this hypothesis, active TGF beta ranging from 1 to 500 ng was administered intrabursally into the ovaries of gonadotropin-primed mice, and the rates of ovum recovery and fertilization were determined. Furthermore, the presence and cellular distribution of endogenous TGF betas and TGF beta type I and type II r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 59 publications
2
10
0
Order By: Relevance
“…The expression of TGFBR1 mRNA has only been studied in antral follicles of mouse, sheep and cow ovaries, and, consistent with our findings, was expressed in the oocyte, GC and TC (Juneja et al 1996, Juengel et al 2004, Feary et al 2007). Similar to the observations made for the ligands in our study, the oocyte was found to abundantly express BMPR1A, BMPR1B, BMPR2 and TGFBR1 mRNA but little variation in mRNA abundance was observed between the different time points.…”
Section: Expression Of Bmps and Bmpr In Pig Folliclessupporting
confidence: 90%
“…The expression of TGFBR1 mRNA has only been studied in antral follicles of mouse, sheep and cow ovaries, and, consistent with our findings, was expressed in the oocyte, GC and TC (Juneja et al 1996, Juengel et al 2004, Feary et al 2007). Similar to the observations made for the ligands in our study, the oocyte was found to abundantly express BMPR1A, BMPR1B, BMPR2 and TGFBR1 mRNA but little variation in mRNA abundance was observed between the different time points.…”
Section: Expression Of Bmps and Bmpr In Pig Folliclessupporting
confidence: 90%
“…TGFb is an important growth factor, which regulates follicular growth, atresia, and maturation of the ovum (Liu et al 1999, Saragueta et al 2002. TGFb is considered to play a dual regulatory role in the function of GCs (Juneja et al 1996). As an important TGFb-activated downstream signaling transduction protein, SMAD3 is found in cultured GCs (Xu et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Tgfbr1 mRNA and protein are expressed by porcine granulosa cells (Goddard et al 1995), whilst TGFBR1 protein is expressed by mouse luteal cells, granulosa cells, theca cells and oocytes (Juneja et al 1996, Gueripel et al 2004). Tgfbr2 mRNA is present in rat ovary (Tsuchida et al 1993), whereas mRNA and protein have been localized to porcine granulosa cells (Goddard et al 1995) and mouse theca, granulosa cells, oocytes and luteal cells (Schmid et al 1994, Gueripel et al 2004.…”
Section: Introductionmentioning
confidence: 99%